“I have nothing more to give”: Disparities in burnout and the protective role of immigrant status during the COVID-19 pandemic - Otuonye, Gene Chibuchim; Shenoi, Nancy; Wu, Tianshi David; Guntupalli, Kalpalatha; Moukaddam, Nidal (Frontiers in Public Health, 2022)
Burnout is an epidemic, with deleterious effects on individuals, patient care, and healthcare systems. The Covid-19 pandemic may be exacerbating this problem. We aimed to explore socio-cultural and gender norms that modulate burnout development in physicians during the pandemic and analyze any disparities associated with gender, marital and immigration status, work-life balance and ethnicity. We conducted an online cross-sectional survey of physicians (August–November, 2021): The Maslach Burnout Inventory for health care professionals (MBI-HSS) was used to measure burnout, combined with a validated survey assessing work-life balance. Demographic data was obtained for each participant. MBI-HSS subscales were measured, along with work and home related changes due to Covid-19. The association between life changes due to Covid-19 and odds of burnout was estimated by logistic regression. Complementary analysis was performed to determine factors most associated with burnout. 352 respondents were analyzed. There was a high prevalence of burnout. Over half of individuals reported a high degree of emotional exhaustion (56%). 83% of individuals reported at least one life factor changed due to Covid-19. Home-related life changes due to Covid-19 were associated with 143% higher odds of emotional burnout (adjusted odds ratio [aOR] 2.43; 95% confidence interval [CI] 1.49, 3.98) after covariate adjusted analysis. High emotional exhaustion was most evident when there were three or more life changes, suggesting a cumulative effect. First-generation immigrants, older physicians, and trainees were identified as protective factors. Although female gender was identified as a factor related to emotional burnout through forward selection, this was not statistically significant (aOR 1.34; 95% CI 0.80, 2.24). Burnout remains pervasive among physicians. We highlight new risk factors for emotional exhaustion (Home-life changes due to Covid-19), and protective factors (first-generation immigrants) not previously explored. Understanding burnout and its disparities allows for improved mitigation strategies, decreasing its deleterious effects.